Original paperGhrelin and its relationship with insulin and insulin resistance in obese hypertensive patients - Dytfeld, Joanna; Pupek-Musialik, Danuta (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2007)
Relationships between ghrelin, gut-derived orexigenic peptide and insulin remain unclear. Insulin resistance, often found in the obese, is accompanied by low ghrelin levels. Aims of the study: 1. Assessment of the relationship between ghrelin and insulin / insulin resistance in obese hypertensive patients and healthy subjects. 2. Evaluation of weight reduction impact on ghrelin and insulin levels. Materials and methods: The study group consisted of 25 obese patients (M/F – 13/12, mean age 45.4±10.4, mean BMI 41.9±9.2 kg/m 2 ). According to IRI/G ratio the study group was divided into two subgroups: meeting the criterion of insulin resistance (subgroup A, n=11) and not meeting this criterion (subgroup B, n=14). Twice, at the begining of the study and after an 8-month, non-pharmacological weight reduction programme, evaluation of plasma total ghrelin and insulin were performed (both using RIA). The control group consisted of 25 healthy controls comparable in age and sex. Results: After weight reduction plasma total ghrelin increased by 229 pg/ml (31.8%). Mean weight loss was 6.4% (7.9 kg). Ghrelin concentrations significantly negatively correlated with fasting insulin and IRI/G ratio. Multivariate regression analysis revealed that in subgroup B fasting insulinaemia remained an independent predictor of fasting ghrelin. Conclusions: In obese persons with arterial hypertension low ghrelin levels are observed. Weight reduction is accompanied by increase in plasma ghrelin level. Negative correlation between ghrelin and insulin in obese hypertensive subjects indicates a potential role of hyperinsulinaemia in forming low ghrelin levels in this group of patients.